CONCERNS FOR PEOPLE THROUGH THE SOCIAL SERVICE PROGRAM IN THE HOLY MONTH OF RAMADHAN BY CADETS OF THE IMMIGRATION POLYTECHNIC OF SURABAYA AND SIDOARJO AREA - Felix Ferdin Bakker; Muhammad Alvi Syahrin (Polteknik Imigrasi, 2021)
Immigration as the spearhead of state sovereignty has an official bond school, namely the Immigration Polytechnic as a place for forging future immigration cadres. Immigration cadets as future generations of immigration leaders are expected not only to have good technical immigration skills but also to have a heart to serve the community. Seeing this, the Immigration cadets for the Surabaya and Sidoarjo regions took the initiative to be able to contribute to social service activities which were held on May 13, 2021 at the Darul Ulum Hikmah Orphanage located in the governorate of Surabaya. It is hoped that this can be continued so that the role of immigration is not only felt in the immigration service but in the social field of immigration standing with the community.